Potential Role of SUMO and SUMOylation in the Pathogenesis of Diabetes Mellitus - Sadeghi, Mahvash; Dehnavi, Sajad; Shohan, Mojtaba; Jamialahmadi, Tannaz; Sathyapalan, Thozhukat; Sahebkar, Amirhossein (Current Medicinal Chemistry, 2023)
Diabetes mellitus is a group of metabolic disorders characterized by hyperglycemia and associated with multiple organ systems complications. The incidence and prevalence of diabetes are increasing in an epidemic proportion worldwide. In addition to environmental factors, some epigenetic and post-translational modifications have critical roles in the pathogenesis of diabetes and its complications. Reversible covalent modification such as SUMOylation by SUMO (Small Ubiquitin-like Modifier) has emerged as a new mechanism that affects the dynamic regulation of proteins. In this review, we initially focus on the function of SUMO and SUMOylation. Subsequently, we assess the potential effects of this process in the pathogenesis of type 1 and 2 diabetes mellitus.
Keywords: SUMO